A COVID-19 e o direito do trabalho: a corrosão das proteções trabalhistas sob o argumento da preservação do emprego e renda - Germano, Rafael Salviati (2022)
On March 11, 2020, the world health organization (who), declared the existence of a pandemic by the new coronavirus, throwing the world into a deep economic crisis, with depression of consumption, production and employment. Consequently (apparent?), there was in Brazil the implementation of legislative measures aimed, at first glance, at the protection of employment and income, as expressly pointed out in article 1º of the provisional measure (MP) of n. 927/2020 and article 1 of MP no. 936/2020 (this is converted into law no. 14.020/2020). However, the research proposes to demonstrate that, through such measures, the protection of jobs is not guaranteed, but the removal of obstacles to the expansion of exploitation on workers’ working hours and income. The intention is to discuss how current capitalism, in the brazilian scenario, has been modulating the relationship between capital and work (neoliberalism from the 1990s, labor reform of 2017 and the normative changes of 2020), especially regarding changes in the legal system. The provisional measures mentioned at the beginning mainly attack three pillars of labor law: the concept of working hours, wages and workers’ union representation. The research is theoretically supported by legal texts, labor doctrine, jurisprudence, legal academic articles and by researchers who draw from the source of labor sociology and political economy, focusing on the marxist line of thought. The apprehension of reality from this thought seems fundamental to a look beyond the consensual neoliberal discourse, which claims that modernizing measures are needed in labor relations (usual euphemism for precariousness), that one must choose between jobs and rights, etc., as if there were no alternative for the workers, only resignation to the growing spoliation. The understanding of the capitalist mode of production and of the legislative transformations discussed, from a critical analysis, indicates the fallacy of that hegemonic discourse, as labor protections only waned in recent decades to meet the needs of capitalist accumulation, having nothing to do with it. With any concern for the workers. The pandemic context emerged as an opportunity to deepen neoliberal measures in Brazil, which the ruling classes do not intend to waste. The research, we think, can contribute to unveil the political-legal fraud that is ordinarily sold to us, showing how the studied norms, despite the veneer of civility and social protection, aim to weaken the bases of labor law, unbalancing even more labor relations.